2009
DOI: 10.1111/j.1468-1331.2008.02523.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐DRB1 and multiple sclerosis in Argentina

Abstract: The present HLA class II population study is in accordance with other Caucasian MS surveys which have found that HLA-DRB1*15 allele is strongly associated with MS disease. In Argentina, this is the first study performed to analyze the association of HLA-DRB1*15 and MS susceptibility in a Caucasian population and therefore contributes with new data to the immunogenomic global MS map.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 12 publications
(19 reference statements)
1
21
0
Order By: Relevance
“…In Caucasians, the HLA-DRB1∗1501 gene appears to confer most of the genetic susceptibility to MS [7]. Although Latin-American populations present singular genetic backgrounds, Argentinean MS patients show HLA class II gene frequencies similar to those observed in Caucasian populations [8]. In addition, genome-wide association studies have now revealed a large number of individual non-HLA genes modestly increasing MS risk [9].…”
Section: Discussionmentioning
confidence: 99%
“…In Caucasians, the HLA-DRB1∗1501 gene appears to confer most of the genetic susceptibility to MS [7]. Although Latin-American populations present singular genetic backgrounds, Argentinean MS patients show HLA class II gene frequencies similar to those observed in Caucasian populations [8]. In addition, genome-wide association studies have now revealed a large number of individual non-HLA genes modestly increasing MS risk [9].…”
Section: Discussionmentioning
confidence: 99%
“…Several genetic loci have been associated with MS or act as modifiers of disease progression, including HLA class II and the DR2 haplotype (HLADRB1 * 15, DQA1 * 01, DQB1 * 06) [92][93][94]. In addition, the IL-2 receptor and IL-7 receptor genes may also play roles in MS [95].…”
Section: Cd24 As a Genetic Modifier For Ms Riskmentioning
confidence: 99%
“…It also raises new and intriguing questions regarding the interplay between environmental and genetic factors in MS. For example, the relative sibling risk ratio remains strikingly similar to that reported in other parts of the world, reflecting perhaps a similar genetic effect, with environmental factors somehow playing a greater role. Alternatively, although the Argentine population is composed mainly of Italian and Spanish immigrants, and HLA-DRB1 allele frequency in MS patients is similar to those reported in Caucasian populations [20], there is a potential role for native genes providing relative protection [21], a topic which needs to be addressed in future studies.…”
Section: Discussionmentioning
confidence: 79%